2002
DOI: 10.2134/jeq2002.1106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Quaternary Ammonium on Sorption of Selected Metal Cations onto Clinoptilolite Zeolite

Abstract: Clay minerals and zeolites have large cation exchange capacities, which enable them to be modified by cationic surfactant to enhance their sorption of organic and anionic contaminants. In this study, the influence of quaternary ammonium surfactants on sorption of five metal cations (Cs+, Sr+, La3+, Pb2+, and Zn2+) onto a clinoptilolite zeolite was investigated. Generally, the metal cation sorption capacity and affinity for the zeolite decreased, indicating that presorbed cationic surfactants blocked sorption s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 27 publications
1
14
0
6
Order By: Relevance
“…The most important clay minerals related to zeolite ores are kaolinite (Al 2 Si 2 O 5 (OH) 4 ), smectites (vermiculite and montmorillonite-(Ca, Na, H)(Al, Mg, Fe, Zn) 2 (Si, Al) 4 O 10 (OH) 2 ·xH 2 O)), and illite ((K, H) Al 2 (Si, Al) 4 O 10 (OH) 2 ·xH 2 O). It is well known that clays exhibit high cation exchange capacities [16]. Several studies have been published on ion exchange of Cs + , U, NH + 4 , K + , Na + , Ca 2+ , and Mg 2+ on several clays such as montmorillonite, vermiculite, and illite [15,17,18].…”
Section: Minerals Found In Zeolite Ores: the Case Of "Impurities"mentioning
confidence: 99%
See 1 more Smart Citation
“…The most important clay minerals related to zeolite ores are kaolinite (Al 2 Si 2 O 5 (OH) 4 ), smectites (vermiculite and montmorillonite-(Ca, Na, H)(Al, Mg, Fe, Zn) 2 (Si, Al) 4 O 10 (OH) 2 ·xH 2 O)), and illite ((K, H) Al 2 (Si, Al) 4 O 10 (OH) 2 ·xH 2 O). It is well known that clays exhibit high cation exchange capacities [16]. Several studies have been published on ion exchange of Cs + , U, NH + 4 , K + , Na + , Ca 2+ , and Mg 2+ on several clays such as montmorillonite, vermiculite, and illite [15,17,18].…”
Section: Minerals Found In Zeolite Ores: the Case Of "Impurities"mentioning
confidence: 99%
“…From the quartz group, clinoptilolite is found along with quartz and cristobalite [16]. Quartz is a neutrally charged inert mineral.…”
Section: Minerals Found In Zeolite Ores: the Case Of "Impurities"mentioning
confidence: 99%
“…Recently, the utilization of natural zeolites, particularly clinoptilolite modified with cationic surfactant (SMZ) with the purpose to remove multiple types of contaminants from water was studied by many researchers especially from Li and Bowman groups [9,10,11,12,13]. Recent study by Campos showed that the modification of mordenite by ethylhexadecyldimethyl ammonium (EHDDMA) and hexadecyltrimethyl ammonium (HDTMA) can remove hexavalent chromium [14].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the adsorption of chromate was promoted in the order of increasing carbon number of organic modifier. The correlation between surfactant tail's chain length and metal ion adsorption was previously investigated by Li et al (2002) who concluded that higher chain length elevated the coverage of clinoptilolite surface due to increased hydrophobic interactions. More recently, Xie et al (2013) have highlighted the effect of ordered chain (all-trans zigzag) conformation, which was also shown to increase as the chain length increased.…”
Section: Classification Of the Surfactants Based On Adsorptive Propermentioning
confidence: 99%